UJI KUALITATIF DAN PERHITUNGAN NILAI RF SENYAWA FLAVONOID DARI EKSTRAK DAUN GULMA SIAM : UJI KUALITATIF DAN PERHITUNGAN NILAI RF SENYAWA FLAVONOID DARI EKSTRAK DAUN GULMA SIAM - Usman, Yusnita; Muin, Rahmatullah (STIKES Nani Hasanuddin Makassar, 2023)
The gulma siam leaves are nuisance plants but are beneficial to human life. In health it is useful as a medicine for wounds, diabetes, coughs and as an antioxidant. It is known that compounds that can heal wounds and antioxidant activity are flavonoid compounds. Research has been carried out to identify the flavonoid compounds of gulma siam leaf extract (Chromolaena odorata L.) by qualitative test and calculation of the retention factor (Rf) value using the thin layer chromatography (TLC) method. This study aims to identify the presence or absence of flavonoid compounds contained in siam weed leaf extract (Chromolaena odorata L.). The gulma siam leaves were dissolved using 70% ethanol solvent with the maceration method which aims to extract the chemical content contained in the Siamese weed leaves. Determination of compounds using two methods, namely qualitative test (reagent test) and calculation of the RF value by thin layer chromatography (TLC). The results showed that Siamese weed leaves contain flavonoid compounds which are marked with a red color change after a qualitative test (reagent test). As for thin layer chromatography (TLC) using ethyl acetate as an eluent: n-hexan (1:1) ethanol extract with Rf value (0.3 cm, 0.55 cm), N-Hexan extract with Rf value (0.27 cm , 0.36 cm) and the H2O extract with an Rf value (0.61 cm, 0.67 cm) positively contained flavonoids marked with blue and green color spots and identified with an Rf Flavonoid value of 0.2-0.75 cm.